Ramper og stilladser – Løft af store sten i oldtiden - Eriksen, Palle (Kuml, 2002)
Ramps and scaffolds The lifting of large stones during antiquity Until well into the 18th century, many scholars thought that megaliths were erected by giants. Less supernatural theories did not occur in print until the 19th century. One of these was expressed in a small pamphlet from 1857, “On the Building Manner of the Passage Graves of the Antiquity”, written by the Danish King Frederik the Seventh. Earlier (1853), the king had been convinced that first the capstones had been placed on a mound and then the uprights had been placed in holes dug out under the capstone (fig. 7). When all uprights were in place, the remaining earth was removed. This so-called mound theory is almost completely forgotten, but it surfaced sporadically in the 20th century, last when J. Osenton was reconstructing dolmens in the Cotswold Hill Quarry by Cheltenham in England in 1996-97. In 1857, Frederik the Seventh put forward the ramp theory, according to which the capstone is pulled up on a ramp to the already finished chamber (fig. 7-8). According to Frederik the Seventh’s proposal, the ramp was built from earth lengthwise covered with timber, on top of which the capstone would have been pulled up on rolls. However, the king had not invented this theory. It was known in Scandinavia and Holland already around 1800. In 1815, N. Westendorf in Holland suggested the use of earth ramps, and the following years the Dutch developed the ramp theory further. Both the early Dutch antiquarians and others referred to the fact that from the 16th to the 19th century (after the Spanish conquest), Inca workers in Peru, when erecting large buildings, used earth ramps for pulling large stones in place. During their golden age (1300-l500 AD), the Incas were masters in building with large stones that weighed up to well over 200 metric tons. Perhaps the know ledge of Inca earth ramps inspired the early European antiquarians to suggest that the megaliths had also been pulled in place by the use of ramps. In 1983, an experiment was carried out in Skånes Djurpark (Scania’s Animal Park) under G. Burenhuldt’s supervision: the building of a long barrow. The capstone was mounted on a wooden sledge and pulled in place using a rope and a 16-m long earth ramp covered with timber lengthwise (fig. 9). The gradient of the ramp was 5 degrees. It took fourteen men a mere twelve seconds to pull op the capstone. In Indonesia, the use of wooden ramps for pulling up grave capstones is well known. Such a situation was docu mented in 1910, when four hundred people pulled the stone in place without the use of rolls (fig. 10-11). In Holland, postholes suggesting the use of a similar method have been found in connection with some megalith graves (fig. 12). When using the scaffold method, one end of the stone is lifted using one or more levers while timber is being pushed under the stone. Then the other end is lifted and timber pushed underneath. The stone is then lifted again, and timber is pushed under in the opposite direction of the previous layer of timber – and so forth, until the stone has reached the planned height (fig. 13-14). The stone is lifted up on a steadily growing scaffold, so to speak. When the lever is high up, ropes are attached to it for pulling. This method was used in Denmark during the 19th century, when the National Museum was placing capstones that had fallen from their original position back onto the megalith graves. In 1897, the Danish archaeologist Sophus Müller suggested that the capstones of the megalith graves had origin ally been positioned in this way. In 1979, J.P. Mohen initiated an experiment in Bougon, France, involving the lifting of a 32-tons copy of a capstone (fig. 15).The lifting was carried out using three levers, each operated by twenty men. By pushing timber under the stone, it was easily lifted one meter. During the same experiment, twenty men easily lifted the stone using a single lever. In 1994, in Ramioul in Belgium, the scaffold method was also used for placing a capston e on a newly built alleé couverte. In Cotswold’s Hill Quarry, England, J. Osenton built three dolmens in 1996-97. A five-ton capstone was lifted one meter by two persons, one using a 3.5-meter long lever, the other pushing timber underneath. Levers are thus very effective, as heavy loads may be lifted using small effort. According to the lever principle, Kl x L1 = K2 x L2, where L1 and L2 are the long and short arm (divided by the fulcrum) respectively, Kl is the force used for pulling, and K2 is the force, which in combination with L2 has an effect on the stone itself. If using a completely regular stone, like an over-sized brick, it will be merely half of the stone’s weight that is lifted, as its edge is resting on the support. However, as the stones are usually irregular, the lifted weight in the following calculations is estimated to be 60% of the total weight. At Cotswold Hill Quarry, the relation between effort and load was 1:100, hence, one man had to pull with a mere power of 30 kg in order to lift the heavy stone. At Bougon, each of the 60 persons had to pull with a force of 32 kilos, if the relation was 1:10, in order to lift the 32-tons block. A capstone in the Spanish passage grave Cueva de Menga weighs 180 metric tons. It could be lifted by 72 men each pulling 50 kg, if the relation was 1:30. It appears that capstones may be easily lifted using a scaffold. When the stones reached the level of the top of the uprights, they could be pulled in over the chamber. At the experiment at Ramioul, Poissonier and Collin used a method in spired by the transportation of stones in a quarry. In the ends of the round timber just under the stone were drilled holes, in which sticks were placed. When the sticks were turned, the stones could be rolled in position over the chamber (fig. 16 ). The use of Stone’s A-frame, which will be mentioned later, would have been very effective indeed, even when very large stones had to be moved from the scaffold onto the chamber. At Stonehenge, the large sarsen stones were erected 2400 BC towards the end of the late Stone Age (fig. 17). The lintels of the large circle weigh approximately seven tons and are positioned at 4.3 meters above the earth. In the middle of the circle is the “horse shoe” consisting of five thrilitons (a thriliton is a pair of uprights carrying a lintel). These lintels weigh up to 16.5 metric tons and are raised seven meters above ground level. In 1924, the engineer E.H. Stone suggested that the lintels had been pulled up an earth ramp that had been so large that it had a platform on top. Here the final adjustment of the lintel could take place using levers. In 1935, another – simpler – technique, the scaffold method, was suggested by colonel R.H. Cunnington. The engineer C.A. Gauld later developed his idea further. He advocated the use of a rather complicated scaffold, which completely surrounded the uprights (fig. 19). In 1991, the engineer P. Pavel carried out an experiment by Strakonice in the Czech Republic (fig. 20). A copy of two uprights in the Stonehenge circle had been erected, and a lintel was to be put in position. The height was 3.5 meters, and the lintel weighed five metric tons. The procedure was surprisingly simple. Using levers and ropes, the stone was pulled up a ramp made from two heavy stems. The pulling was done in 30-cm tugs, and behind the lintel was a“brake rod”, which was moved along to prevent th e stone from sliding down. The levers were of spruce, 4.5 m long and 25 cm in diameter. The ropes were 3 cm thick. The stone was pulled up in three days by ten men. In 1994, M. Whitby was carryin g out experiments near Stonehenge. They included the placin g of lintels using both ramp and scaffold. For this purpose, concrete copies of two uprights and a lintel had been made. The lintel weighed ten metric tons and had to be lifted seven meters. First, it was lifted using the scaffold method. As this went easily, and it was obvious that it could be easily lifted in place, the experiment was called off The scaffold was a simple one, which did not surround the uprights. The lintel was pulled up a metal ramp, which served as an earth ramp. On the surface, the ramp had three tracks of timber lengthwise, and 90 people pulled up the stone in three ho urs. T he pu llin g was don e usin g an A-frame, which works as an upright lever (fig. 21). E.H. Stone had suggested this method in 1924 when the uprights were erected (fig. 22). Whitby’s experiment had the special point that the timber on the ramp surface was separated at the top, so that it would tip with the stone when it reached the top. One or the other? A ramp or a scaffold? The huge disadvantage of the earth ramp is that it would have taken a very long time to both build it and remove it. It would be faster and easier to use Pavel’s wooden ramp, strengthened and supported by timber and then pull up the stone either using Pavel’s method or an A-frame. Finally, there is the scaffold method, which Whitby and Richards found very rewarding. However, this method seems too simple and undramatic as opposed to the ramps. At any rate, many scholars have become obsessed by the ramps and will not consider the scaffold as an alternative. The theories of how Egypt’s large pyramids were erected are a fine example of this. The Great Pyramid was build for the Pharaoh Cheops, who died around 2580 BC. It is an impressive monument, which was originally 146.5 meters high, with each side measuring 230 meters. It was built from 2.300.000 box-shaped stones, each weighing approximately 2.5 metric tons or less. How the Egyptian pyramids were built is still a matter of speculation. The many suggested methods can be divided into two groups: ramps or gradual raising using levers (the scaffold method). The ramp method is preferred by most, but the shape of the ramps remains a mystery (fig. 23). Ramps have been found next to some very small and unfinished pyramids, but they were less than seven meters high. These ramps were made from limestone rubble, sand, gypsum, and clay. It seems obvious that ramps may have been used for the building of small pyramids and for the lower parts of larger pyramids. However, in the case of the great pyramids, the ramps would gradually become very steep and very long, or both, when the pyramid rose upwards. In his book, “The Complete Pyramids” (1997), Mark Lehner, one of the leading pyramid scholars, strongly advocates the ramp theory. In 1996, he took part in the building of a 6-m high pyramid “to test some of the current theories of armchair pyramid builders and try out ancient theories”. The small pyramid was built using a ramp. The scaffold method was also tested for the raising of a stone weighing two metric tons. The experiment was unsuccessful and therefore dismissed. However, elementary mistakes were made, as for instance using boards stacked in layers as a substitute for heavy timber. In spite of this, there are in fact numerous advantages of lifting the stones step by step. For instance,several teams can work simultaneously on each step; the distance is shorter; there is no long return with an empty sledge; and huge ramps do not have to be built and removed again .When Herodotus visited The Great Pyramid around 440 BC, he was told that it had been built by lifting the stones step- by-step using special devices (mechania). This information was omitted in “The Complete Pyramids”. The method used for building a large pyramid could have been a combination of the two techniques. Ramps were used at first, until they became too large or steep or both, then stones were lifted step- by-step using levers. This change may well have taken place at a height of 50 meters, when 72% of the stone mass was already in place. Also, the use of ramps and scaffolds does not have to be an either/or. Perhaps both methods were used. The heavy bluestones at Stonehenge, each weighing between 3 and 4 metric tons, were quarried in antiquity in the Preseli Mountains in Wales. The 80 bluestones were transported more than 350 km across land and water. In 2000, a group of volunteers wanted to repeat this great achievement of the past by transporting a 3-ton stone along the same route. The project, called The Millenium Stone, was a total failure and had to be given up. The participants met too many obstacles on the way and had to use modern techniques; the stone was transported far shorter distances a day than expected; a crane had to be used for lifting the stone on to a vessel, which later sank in 17 meters of water. One important reason for the poor out come was not just the lack of technical skills, but also lack of planning, expertise, and motivation among the participants. These factors are indeed the prerequi site for a successful implementation, in the past as well as now. The experiments at Bougon, Cotswold, and Strakonice showed that a few people were able to lift the stones. However, in the antiquity this would have taken place at community events, which gathered huge crowds. This was certainly the case when dolmens were built in Indonesia in modern time. Here, the presence of many people gave prestige to the organizers, who in return demonstrated their wealth and hospitality by throwing large parties where the guests were lavishly entertained. For both organizers and participants these occasions offered the possibility of making or renewing agreements and alliances. One of the many reasons behind the erection of the megalith graves was its stabilizing effect on society. The megalith builders would have been highly motivated and very determined, as the balance of their social and spiritual universe depended on a successful completion of the work with the huge stones. The muscle power of hundreds of men is not enough; it also takes a foreman with ingenuity, coordination and determination (fig. 24). The foremen of the English archaeologist, C.L. Woolley, were good at moving large stones. Once, Woolley showed his foreman, the Arab Hamoudi, the large stone, measuring 21.5 x 4.3 x 4.2 meters, which during the first century AD was placed at seven meter’s height in the wall of Acropolis in Baalbek in Syria. “He sat in silence, looking at it for perhaps twenty minutes, and then rose to his feet.‘I must go away,᾿ he said,‘my head aches᾿; and as he went, I heard him murmur: ‘By Allah, what a foreman!᾽” In this context, Woolley mentions that at his time (1953), such a stone could not be lifted that high by machines, but that the people of the antiquity were able to do it because they lacked machines! Palle Eriksen Ringkøbing Museum Translated by Annette Lerche Trolle